2019
DOI: 10.1186/s12891-019-2885-5
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous and subsequent long-term oral tranexamic acid in enhanced-recovery primary total knee arthroplasty without the application of a tourniquet: a randomized placebo-controlled trial

Abstract: BackgroundTo assess the efficacy and safety of intravenous and subsequent long-term oral tranexamic acid (TXA) following total knee arthroplasty (TKA) without a tourniquet.MethodsIn this double-blinded trial, 118 patients undergoing primary TKA were randomized into two groups: the patients in group A received intravenous TXA at 20-mg/kg 10 min before the surgery and 3 h postoperatively, and then oral 1 g TXA from postoperative day (POD) 1 to POD 14, and the patients in group B received intravenous TXA at 20-mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 59 publications
3
39
0
Order By: Relevance
“…al. (23). As can be seen from the results of this study, the pain during the follow-up period has been greatly reduced compared with before the operation.…”
Section: Discussionsupporting
confidence: 49%
“…al. (23). As can be seen from the results of this study, the pain during the follow-up period has been greatly reduced compared with before the operation.…”
Section: Discussionsupporting
confidence: 49%
“…The application of tourniquet in total knee arthroplasty can effectively reduce intraoperative bleeding, provide a clean and clear surgical eld, and also facilitate the application of bone cement technology [6], but its postoperative complications such as early postoperative pain, lower limb swelling, and tension blisters make its use value controversial [7,8]. As the concept of enhanced recovery was put forward [9][10][11], more and more scholars proposed the restrictive use of tourniquets as well as the optimal use of tourniquets [12][13][14] There are a wide variety of studies on tourniquets, such as the timing of tourniquet release [15,16], the location of tourniquet installation and the pressure of tourniquet [17], and the timely and long tim ing of tourniquet use [18], and most scholars agree that the length of tourniquet use has a signi cant correlation with postoperative complications: Barker, T et al [19] concluded that the use of tourniquets for more than 100 min in total knee arthroplasty will increase the risk of postoperative wound infection, deep vein thrombosis, pulmonary embolism, and nerve injury. Jawhar et al [20] found that surgery longer than 120 min with a tourniquet increased the risk of deep ve in thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our research focus has always been on blood loss reduction during orthopedic surgery. Patients who have not developed anemia and have higher hemoglobin levels show better performance during rehabilitation training and may have additional bene ts such as a better QoL 8,27 . An effective blood preservation strategy is the key to ERAS after orthopedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Anti brinolytic therapy, an important aspect of blood management that is considered to be closely related to the concept of enhanced recovery after surgery (ERAS), has emerged as a particular research focus 7,8 .…”
Section: Introductionmentioning
confidence: 99%